Agricultural Commodity Price Shocks and Their Effect on Growth in Sub‐Saharan Africa. (30th August 2015) - Addison, Tony; Ghoshray, Atanu; Stamatogiannis, Michalis P.
Abstract: Commodity price shocks are an important type of external shock and are often cited as a problem for economic growth in Sub‐Saharan Africa. We choose nine Sub‐Saharan African countries that are heavily dependent on a single agricultural commodity for a significant portion of their income. This paper quantifies the impact of agricultural commodity price shocks using a structural non‐linear dynamic model. The novel aspect of this study is that we determine whether the response of per capita GDP for the selected Sub‐Saharan African countries is different to unexpected increases in agricultural commodity prices as opposed to decreases in prices. We conclude that there is very little evidence that an unanticipated price increase (decrease) will lead to a significantly different response in per capita incomes.